2019
DOI: 10.2196/11718
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of a Remote Web-Based Daily Diary Study Examining Sexual Minority Stress, Relationship Factors, and Alcohol Use in Same-Sex Female Couples Across the United States: Study Protocol of Project Relate

Abstract: Background The Healthy People 2020 initiative aims to reduce health disparities, including alcohol use, among sexual minority women (SMW; eg, lesbian, bisexual, queer, and pansexual). Compared with heterosexual women, SMW engage in more hazardous drinking and report more alcohol-related problems. Sexual minority stress (ie, the unique experiences associated with stigmatization and marginalization) has been associated with alcohol use among SMW. Among heterosexuals, relationship factors (eg, partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…Participants were recruited as part of a larger study examining daily sexual minority stressors, relationship factors, and alcohol use (among other health behaviors) in same-sex female couples (Heron et al, 2019). Eligibility criteria for all participants were: Age 18–35, self-identify as a cisgender woman, currently in a relationship with a woman for 3+ months, see partner at least once per week, and able to complete a daily survey each morning.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited as part of a larger study examining daily sexual minority stressors, relationship factors, and alcohol use (among other health behaviors) in same-sex female couples (Heron et al, 2019). Eligibility criteria for all participants were: Age 18–35, self-identify as a cisgender woman, currently in a relationship with a woman for 3+ months, see partner at least once per week, and able to complete a daily survey each morning.…”
Section: Methodsmentioning
confidence: 99%
“…Each participant could receive up to $77 for her participation ($25 USD for completing the baseline survey, $3 USD for each daily survey, and $10 USD as a bonus for completing at least 80% of the daily surveys). Additional procedural details for the larger study are reported elsewhere (17).…”
Section: Methodsmentioning
confidence: 99%
“…The written materials corresponded to the information as what was presented in the videos, and both conditions included information similar to what would be presented to participants as part of the screening/ recruitment process and informed consent process of an in-person study that involved EMA methods. The written content that was presented to all participants is available as part of the larger study protocol (17). Based on the written materials, five videos were professionally developed.…”
Section: Written and Video Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although same-sex couples were allowed to participate in our studies, the numbers were so small that analyses were limited to mixed-sex couples. Given recent expansion of research to include gender minority samples and recognition of the need to understand the role of alcohol in same-sex IPV (Shorey et al, 2019), a few daily report studies involving substance use and relationship functioning are currently being conducted using gender minority individuals (Shorey et al, 2020) and same-sex couples (Heron et al, 2019;Parrott, 2018Parrott, -2021. However, to date, no current or published studies have compared mixed-sex to same-sex couples with respect to daily relationship functioning or the role of alcohol in couple conflict and aggression.…”
Section: Acute Effects Of Substance Use Episodes On Intimate Partner Violencementioning
confidence: 99%